Bread Broken and Scattered: The World Church and Biblical Interpretation - Lindsay, Dennis R. (Stone-Campbell journal, 2007)
As a model for Scripture the church at-large, or world church, reflects the universality of the Christian canon, as well as the diversity, inner tensions, and even contradictions apparent within the constituent units of the canon. As the Bible is read, heard, and sacramentally performed within the context of the world churchand especially within the context of the Eucharist celebrationthe diverse voices in Scripture are allowed to converge, contradictions may be faced and tensions embraced, and the possibility for a holistic approach to biblical interpretation promises to emerge.